Development of enzymatic zinc-air biofuel cell using laccase - Abdul Aziz bin Ahmad (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
A hybrid biofuel cell, a zinc-air cell employing laccase as the oxygen reduction catalyst is investigated. The bioelectrochemical system combines the well-understood zinc-air cell and an enzymatic biofuel cell - an electropositive zinc element is coupled with the biocatalytic activity of the laccase enzyme. As a result, the biofuel cell design is simplified since the anolyte components (enzyme, substrate, electron mediator and buffer solution) are replaced with a metallic zinc. Based on the zinc-air system, an air electrode is utilized in the cell design. The air electrode serves both as the cathodic current collector as well as to feed ambient oxygen continuously into the system through its porous structure. A single compartment or membraneless cell design is adopted in this work. The cell electrolyte consists of laccase and syringaldazine in potassium dihydrogen phosphate buffer of pH 6.5. Laccase, sourced from Rhus vernicifera, serves as the biocatalyst for the electroreduction of oxygen from the ambient air, while syringaldazine acts as the phenolic substrate for laccase. Unlike most biofuel cells, in the present work laccase enzyme is left to be freely suspended in the buffer electrolyte. Besides, the cell is operated under open ambient conditions. The fabricated cell is characterised based on its open-circuit voltage, power density profile and galvanostatic discharge. Various aspects of cell design – the use of air electrode, syringaldazine as an enhancer, charge leakage phenomenon and the use of high surface area electroplated zinc anode, are also investigated. The activity of laccase as an oxidoreductase is clearly prevalent from the cell discharge profiles. The zinc-air biofuel cell registered an open-circuit voltage of 1.2 V and capable to generate a maximum power density of 3.28 mW at 0.4 V and 8.5 mA. The highest cell capacity obtained is 7.5 mAh. Despite its simple design features and operated not under controlled conditions, the hybrid biofuel cell studied demonstrated power output of comparable performance to that of biocatalytic cells utilising a much more complex system design – immobilized enzyme, controlled temperature and humidity, oxygenated electrolyte etc. The results of this work shall serve as a reference for biofuel cell research to evaluate the efficacy of immobilizing enzymes onto electrodes. Furthermore, the developed biofuel system employing freely suspended enzyme is applicable for microbial fuel cell.